PENGARUH PROFESIONALISME KERJA PEGAWAI TERHADAP KUALITAS PELAYANAN WAJIB PAJAK (PERUSAHAAN) PADA KANTOR PELAYANAN PAJAK PRATAMA KOTA KENDARI) - tania, tania; yusuf, muhammad (Universitas Halu Oleo, 2017)
This study aims: To determine the effect of Employee Work Professionalism on Taxpayer Service Quality (Company) at the Primary Tax Office of Kendari City. The benefits of this research are as thought or information material in conducting research on Employee Work Professionalism on Taxpayer Service Quality, as information and study material for comparison to other researchers who have anything to do with this research. The sample of respondents in this study amounted to 30 people consisting of 25 corporate taxpayers and 5 employees of the Primary Tax Office of Kendari City. This study uses simple linear regression analysis. The results showed that the work professionalism of employees had a significant effect on the Quality of Taxpayer Services (Companies) at the Primary Tax Office of Kendari City